Effective Packaging Design as an Empowerment Strategy for Household MSMEs: A Participatory Learning and Action Approach - Harti, Adi Oksifa Rahma; Marina, Ida; Sujadi, Harun; Fahrudin, Muhammad; Fitria, Anis Nurul (Pascasarjana Universitas Mataram, 2024)
Empowering Household Micro, Small, and Medium Enterprises (MSMEs) is a primary focus in local economic development and community economics. One crucial aspect in enhancing the competitiveness and capabilities of Household MSMEs is effective packaging design. Packaging design is not merely about visual aesthetics but also about functionality and interaction with consumers. The Participatory Learning and Action (PLA) method is utilized to develop effective packaging designs, involving MSME actors, consumers, and other relevant parties. This PLA approach is expected to assist Household MSMEs in facing tight market competition. This research proposes community empowerment activities through the production of Rempeyek products in one of the MSMEs in Majalengka, using the PLA method. The success evaluation of the activities is conducted through the four-level evaluation model (Kirkpatrick), covering reaction, learning, behavior, and results. The evaluation results show an improvement in participants' knowledge, understanding, and skills in packaging design. The overall scores indicate that these activities successfully achieve the Kirkpatrick evaluation goals. Recommendations to enhance the implementation of this service development include increasing the capacity of project participants, addressing deeper issues, local government support, and support for domestic industries. This research demonstrates that training and mentoring in packaging design can provide significant benefits to Household MSMEs, enhancing product quality, market value, and competitiveness in a competitive market.